(untitled) (Bangladesh Journal of Agricultural Research, 2016)
An experiment was conducted to find out the influence of three irrigation levels (no irrigation, one irrigation and two irrigation) on four mustard varieties (Tori- 7, BARI Sharisha-6, BARI Sharisha-9 and BARI Sharisha-8). The non-irrigated plots had highest aphid population (34.96/plant) and lowest (11.16 aphids/plant) in two irrigation. The variety BARI Sharisha-8 showed lowest (5.34 aphids/plant) aphid infestation and its yield was highest (2.05 ton/ha). Interaction effects indicated that the crop escaped from the aphid incidence in the variety BARI Sharisha-8 irrigated 2 times and produced highest yield (2.37 ton/ha). The differences in the aphid population at three irrigation levels affected the yield contributing characters and it was negatively correlated (correlation coefficient value r ranged from -0.91 to 1.0). Bangladesh J. Agril. Res. 41(4): 625-632, December 2016